A pea variety ‘Kazak’ - A. R. Ashiev; K. N. Khabibullin; M. V. Skulova; N. S. Kravchenko (Зерновое хозяйство России)
Peas is one of the most common leguminous crops, the value of which is determined by a wide range of use. Traditional pea varieties often suffer from poor productivity and insufficient tolerance to adverse weather conditions such as drought, frost, and diseases. Modern plant breeding has made it possible to develop new leafless pea varieties with a determinate growth type (limited stem growth), which significantly simplifies mechanized harvesting. In this regard, the purpose of the current study was to develop a new highly productive pea variety with resistance to extreme environmental conditions and high feed and food qualities. During a long-term breeding work, including a various initial forms’ crossing, a selection of the best genotypes and a strict control of productivity and stability parameters, the variety ‘Kazak’ was studied in the Competitive Variety Testing under number G-1122 in 2020–2022. The yield structure elements have shown that pea seed productivity has increased due to all elements of seed productivity. Number of productive beans per plant of the variety ‘Kazak’ was 4.9 pcs., number of seeds per plant was 16.3 pcs., 1000-seed weight was 206.7 g, productivity of one plant was 3.4 g, and protein in seeds was 25%. Due to higher indicators of the yield structure elements, it was possible to form productivity from 2.40 to 4.41 t/ha, which is on average 0.50 t/ha higher than that of the standard (2.07–3.42 t/ha). Economic efficiency of the variety cultivation has shown an additional output of 10,110 rubles per hectare, and the profitability level was 70.6%. Further work is going to be aimed at the study of adaptive potential of the variety in various climatic areas and the features of varietal agricultural technology to achieve maximum productivity. Particular attention is going to be paid to the study of genetic potential of the variety ‘Kazak’ for breeding new, even more productive and resistant pea varieties.